Mapping indigenous California: Agency and tribal perspectives on ancestral territorial representation - Seth LaRosa; Van Butsic; Jeremy Sorgen; Peter Nelson; Jennifer Sowerwine (Land Use Policy, 2026)

Assessing the effectiveness of strictly protected areas in preventing forest loss and degradation across different forest types in the Caucasus - Johanna Buchner; Katarzyna Ewa Lewińska; Van Butsic; Zuzana Buřivalová; Arash Ghoddousi; Natalia Rogova; Afag Rizayeva; Eugenia V. Bragina; Volker C. Radeloff (Biological Conservation, 2026)

The emerging need to manage scavenged wildlife resources - Samantha Maher; Tyler Kjorstad; Kailin Kroetz; Van Butsic; Arthur D. Middleton (Biological Conservation, 2025)

Assessing land use change trajectories following food insecurity shocks in 25 low- and middle-income countries - Evan Patrick; Van Butsic; Matthew D. Potts (Global Environmental Change, 2025)

Unchecking the box: Overcoming barriers to meaningful consultation - Jeremy Sorgen; Peter Nelson; Van Butsic; Seth LaRosa; Shasta Gaughen; Earl Crosby; Robert Geary; Jennifer Sowerwine (Environmental Science & Policy, 2025)

Effectiveness of protected areas in the Caucasus Mountains in preventing rangeland degradation - Arash Ghoddousi; Marie Pratzer; Katarzyna E. Lewinska; Juliana Eggers; Benjamin Bleyhl; Hüseyin Ambarli; Marine Arakelyan; Elshad Askerov; Van Butsic; Astghik Ghazaryan; Bejan Lortkipanidze; Volker C. Radeloff; et al. (Conservation Biology, 2025)
As land use intensifies globally, it increasingly exerts pressure on protected areas. Despite open, nonforested landscapes comprising up to 40% of protected areas globally, assessments have predominately focused on forests, overlooking the major pressures on rangelands from livestock overgrazing and land conversion. Across the southern Caucasus, a biodiversity hotspot extending over 5 countries, we conducted a broadscale assessment of the extent to which protected areas mitigate land‐use pressure on rangelands in them. Using satellite‐based indicators of rangeland vegetation greenness from 1988 to 2019, we assessed the effectiveness of 52 protected areas. This period encompassed the collapse of the Soviet Union, economic crises, armed conflicts, and a major expansion of the protected area network. We applied matching statistics combined with fixed‐effects panel regressions to quantify the effectiveness of protected areas in curbing degradation as indicated by green vegetation loss. Protected areas were, overall, largely ineffective. Green vegetation loss was higher inside than outside protected areas in most countries, except for Georgia and Turkey. Multiple‐use protected areas (IUCN categories IV–VI) were even more ineffective in reducing vegetation loss than strictly protected areas (I & II), highlighting the need for better aligning conservation and development targets in these areas. Mapping >10,000 livestock corrals from satellite images showed that protected areas with a relatively high density of livestock corrals had markedly high green vegetation loss. Ineffectiveness appeared driven by livestock overgrazing. Our key finding was that protected areas did not curb rangeland degradation in the Caucasus. This situation is likely emblematic of many regions worldwide, which highlights the need to incorporate degradation and nonforest ecosystems into effectiveness assessments.

The geography of social vulnerability and wildfire occurrence (1984–2018) in the conterminous USA - Ronald L. Schumann; Christopher T. Emrich; Van Butsic; Miranda H. Mockrin; Yao Zhou; Cassandra Johnson Gaither; Owen Price; Alexandra D. Syphard; Joshua Whittaker; Sanam K. Aksha (Natural Hazards, 2024)

Where money grows on trees: A socio-ecological assessment of land use change in an agricultural frontier - Phoebe Parker-Shames; Hekia Bodwitch; Justin S. Brashares; Van Butsic (Landscape and Urban Planning, 2023)

Farm consolidation and turnover dynamics linked to increased crop diversity and higher agricultural input use - Olivia Hemond; Van Butsic; Diana Moanga; Ariani C. Wartenberg (Agricultural Systems, 2023)

Assessing the ecosystem services and disservices provided by migratory wildlife across the Greater Yellowstone Ecosystem - Samantha M.L. Maher; Kristin J. Barker; Kailin Kroetz; Van Butsic; Bryan Leonard; Arthur D. Middleton (Biological Conservation, 2023)

After legalization: Cannabis, environmental compliance, and agricultural futures - Michael Polson; Hekia Bodwitch; Eric Biber; Van Butsic; Theodore Grantham (Land Use Policy, 2023)

Quantifying drivers of change in social-ecological systems: land management impacts wildfire probability in forests of the western US - Katherine J. Siegel; Laurel Larsen; Connor Stephens; William Stewart; Van Butsic (Regional Environmental Change, 2022)

Effects of ecotourism on forest loss in the Himalayan biodiversity hotspot based on counterfactual analyses - Jodi S. Brandt; Volker Radeloff; Teri Allendorf; Van Butsic; Anand Roopsind (Conservation Biology, 2019)
Ecotourism is developing rapidly in biodiversity hotspots worldwide, but there is limited and mixed empirical evidence that ecotourism achieves positive biodiversity outcomes. We assessed whether ecotourism influenced forest loss rates and trajectories from 2000 to 2017 in Himalayan temperate forests. We compared forest loss in 15 ecotourism hubs with nonecotourism areas in 4 Himalayan countries. We used matching statistics to control for local‐level determinants of forest loss, for example, population density, market access, and topography. None of the ecotourism hubs was free of forest loss, and we found limited evidence that forest‐loss trajectories in ecotourism hubs were different from those in nonecotourism areas. In Nepal and Bhutan, differences in forest loss rates between ecotourism hubs and matched nonecotourism areas did not differ significantly, and the magnitude of the estimated effect was small. In India, where overall forest loss rates were the lowest of any country in our analysis, forest loss rates were higher in ecotourism hubs than in matched nonecotourism areas. In contrast, in China, where overall forest loss rates were highest, forest loss rates were lower in ecotourism hubs than where there was no ecotourism. Our results suggest that the success of ecotourism as a forest conservation strategy, as it is currently practiced in the Himalaya, is context dependent. In a region with high deforestation pressures, ecotourism may be a relatively environmentally friendly form of economic development relative to other development strategies. However, ecotourism may stimulate forest loss in regions where deforestation rates are low.

The effect of protected areas on forest disturbance in the Carpathian Mountains 1985–2010 - Van Butsic; Catalina Munteanu; Patrick Griffiths; Jan Knorn; Volker C. Radeloff; Juraj Lieskovský; Daniel Mueller; Tobias Kuemmerle (Conservation Biology, 2017)
Protected areas are a cornerstone for forest protection, but they are not always effective during times of socioeconomic and institutional crises. The Carpathian Mountains in Eastern Europe are an ecologically outstanding region, with widespread seminatural and old‐growth forest. Since 1990, Carpathian countries (Czech Republic, Hungary, Poland, Romania, Slovakia, and Ukraine) have experienced economic hardship and institutional changes, including the breakdown of socialism, European Union accession, and a rapid expansion of protected areas. The question is how protected‐area effectiveness has varied during these times across the Carpathians given these changes. We analyzed a satellite‐based data set of forest disturbance (i.e., forest loss due to harvesting or natural disturbances) from 1985 to 2010 and used matching statistics and a fixed‐effects estimator to quantify the effect of protection on forest disturbance. Protected areas in the Czech Republic, Slovakia, and the Ukraine had significantly less deforestation inside protected areas than outside in some periods; the likelihood of disturbance was reduced by 1–5%. The effectiveness of protection increased over time in these countries, whereas the opposite was true in Romania. Older protected areas were most effective in Romania and Hungary, but newer protected areas were more effective in Czech Republic, and Poland. Strict protection (International Union for Conservation of Nature [IUCN] protection category Ia‐II) was not more effective than landscape‐level protection (IUCN III‐VI). We suggest that the strength of institutions, the differences in forest privatization, forest management, prior distribution of protected areas, and when countries joined the European Union may provide explanations for the strikingly heterogeneous effectiveness patterns among countries. Our results highlight how different the effects of protected areas can be at broad scales, indicating that the effectiveness of protected areas is transitory over time and space and suggesting that generalizations about the effectiveness of protected areas can be misleading.

Analytical Solutions to Trade‐Offs between Size of Protected Areas and Land‐Use Intensity - VAN BUTSIC; VOLKER C. RADELOFF; TOBIAS KUEMMERLE; ANNA M. PIDGEON (Conservation Biology, 2012)
Land‐use change is affecting Earth's capacity to support both wild species and a growing human population. The question is how best to manage landscapes for both species conservation and economic output. If large areas are protected to conserve species richness, then the unprotected areas must be used more intensively. Likewise, low‐intensity use leaves less area protected but may allow wild species to persist in areas that are used for market purposes. This dilemma is present in policy debates on agriculture, housing, and forestry. Our goal was to develop a theoretical model to evaluate which land‐use strategy maximizes economic output while maintaining species richness. Our theoretical model extends previous analytical models by allowing land‐use intensity on unprotected land to influence species richness in protected areas. We devised general models in which species richness (with modified species‐area curves) and economic output (a Cobb–Douglas production function) are a function of land‐use intensity and the proportion of land protected. Economic output increased as land‐use intensity and extent increased, and species richness responded to increased intensity either negatively or following the intermediate disturbance hypothesis. We solved the model analytically to identify the combination of land‐use intensity and protected area that provided the maximum amount of economic output, given a target level of species richness. The land‐use strategy that maximized economic output while maintaining species richness depended jointly on the response of species richness to land‐use intensity and protection and the effect of land use outside protected areas on species richness within protected areas. Regardless of the land‐use strategy, species richness tended to respond to changing land‐use intensity and extent in a highly nonlinear fashion.